Catalytic converter theft: An emerging risk factor for carbon monoxide poisoning - Ahna H. Weeks; Suzan Mazor; Anita A. Thomas (JEM Reports)
Background: Carbon monoxide (CO) poisoning is associated with high morbidity and mortality. Diagnosis can be challenging for the encountering physician due to vague and nonspecific presenting signs and symptoms. Confirmatory testing is typically prompted by historical information identifying a key exposure or risk factor. Case report: A patient presented to the emergency department after having a seizure. The patient was diagnosed with CO poisoning, with a carboxyhemoglobin level of >20.9 ​%, caused by unintentional exposure to motor vehicle exhaust while idling in his car after his catalytic converter was stolen. The patient was transferred to a hospital with the capacity for treatment with hyperbaric oxygen.Why should an emergency physician be aware of this? Increasing prevalence of catalytic converter theft puts people at risk for CO poisoning. Emergency physicians should consider CO poisoning broadly, especially in urban environments with high rates of petty crime.